OPTIMALISASI LIVE STREAMING DAN FLASH SALE TIKTOK–TOKOPEDIA UNTUK PRODUK WARDAH - Pernando Suherman, Perry; Siswandi, Zerry; haditya, Iqbal (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
Advancements in digital technology have driven major transformations in the commerce sector, particularly through the integration of TikTok Shop features into the Tokopedia ecosystem. This study aims to empirically examine and analyze the effects of live streaming effectiveness and flash sales on purchase decisions for Wardah cosmetic products on the TikTok–Tokopedia platform. Using a quantitative method with a causal research design, the study involved 100 respondents in the Sukabumi area selected through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS 3 software. The results indicate that live streaming effectiveness has a positive and significant effect on purchase decisions, with a t-statistic value of 4.587 and a path coefficient of 0.492. In addition, the flash sale strategy is also proven to have a significant effect on purchase decisions, with a t-statistic of 4.498 and an identical path coefficient. The R² value of 0.939 suggests that 93.9% of the variance in purchase decisions can be explained by these two variables, while the Q² value of 0.659 confirms that the model has very strong predictive relevance. These findings conclude that optimizing real-time interaction and urgency-based promotions is crucial in driving consumer purchase decisions in the digital era.